Designing of Web-Based Learning Media for Senior High School During The Covid-19 Pandemic - Haryani, Haryani; Saputra, Dedi (CV. Inara, 2021)
The learning process of Senior High School level is done by various methods. In the current pandemic condition, a learning process is needed that is implemented with strict health protocols. One alternative method of the effective and online learning processes is by learning to use web-based learning media. The creation of learning media in this study uses a prototype model, which consists of listening to needs, building mock-ups and evaluating mock-ups. As a sample of research is SMAS Wiyata Mandala Balai Batang Tarang, with data collection techniques used consisting of interviews, observations and library studies. The media designed in this study provides facilities to three (3) level users, namely administration, teachers and students. Administration can manage administrative data, majors, subjects, classes, students, teachers, teaching teachers, announcements and access student achievement reports. Teachers can manage to manage teaching materials, problem banks, meeting schedules and access student achievement reports. Students can access modules, work on weekly meeting questions and access the grades in the meeting results. This designed learning media is expected to help SMAS Wiyata Mandala Balai Batang Tarang in carrying out the learning process and can improve student achievement even in the midst of the pandemic.